2004
DOI: 10.2307/3583187
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities: Emergency Contraception Utilisation by Young South African Women

Abstract: Although contraceptives, including emergency contraceptives, are widely available free at public health facilities in South Africa, rates of teenage and unintended pregnancy are high. This paper analyses awareness and utilisation of emergency contraception amongst 193 young women (aged 15-24 years) attending public sector health facilities. Structured interviews were held at 17 and 14 primary health clinics in an urban and a rural area respectively. Respondents were asked about their knowledge of contraceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 7 publications
0
26
1
Order By: Relevance
“…Women preference for injectable contraceptive has been attributed to its relatively long duration of action (at least 2 months) and the possibility of keeping their husbands out of the picture should they disagree on use of modern contraceptives (Kebede, 2006;Mqhayi et al, 2004). Contrary to the finding in this study, a recent health facility based study in Sokoto (the study area) reported implant as the most commonly used contraceptive among the women studied (Shehu and Burodo, 2013).…”
Section: Discussioncontrasting
confidence: 55%
“…Women preference for injectable contraceptive has been attributed to its relatively long duration of action (at least 2 months) and the possibility of keeping their husbands out of the picture should they disagree on use of modern contraceptives (Kebede, 2006;Mqhayi et al, 2004). Contrary to the finding in this study, a recent health facility based study in Sokoto (the study area) reported implant as the most commonly used contraceptive among the women studied (Shehu and Burodo, 2013).…”
Section: Discussioncontrasting
confidence: 55%
“…Indeed, most studies suggest that very few people have even heard of it [13][14][15] . A study of adolescent mothers in one South African province, for example, found that approximately one fifth knew about the existence of EC and that even fewer knew that ECPs could be taken to prevent pregnancy after unprotected intercourse 13 .…”
Section: Awareness Of Emergency Contraceptionmentioning
confidence: 98%
“…30 Many researchers have concluded that expanded access does not increase the rate of unprotected sexual intercourse nor does it change sexual behaviours. 31,32 All these disbeliefs leads to directly obtain it from pharmacy than to consult health personnel so as to maintain privacy leading to failure and ending into unsafe abortion specially in young unmarried females.…”
mentioning
confidence: 99%